Consumer knowledge of food labeling - Michalina Rakuła; Agata Kiciak (Kazimierz Wielki University, 2022)
Introduction: Food labels are an important source of information for consumers about the food they consume. They are divided into compulsory and voluntary. Compulsory information are name, composition, additives, expiry date, nutritional value and also country and place of origin. Voluntary information are brand, quality marks, nutrition and health claim and different graphical signs making it easier to recognize the product. Aim: The aim of this paper is to evaluate the knowledge of consumers in information placed on the labels of food products and evaluating which sociodemographic factors influence the level of knowledge of respondees. Material and methods: The research was performed in the period of February to April 2022 with the help of an original questionnaire among 212 residents of Poland. After analyzing the answers, the level of knowledge of the respondents was assessed. Finally, the level of knowledge was compared to gender, age and education level. Results: 39,6% of responders read labels, 31,6% read only specific information. Both women (44,4%) and men (35,6%) most commonly showed knowledge on a good level. Older people aged 51-70 (38.1%) are characterized by a lower level of knowledge. People with vocational education demonstrate a sufficient level of knowledge (45,4%), and the highest level - very good - among people with university education (50%). Conclusions: The awareness of the most numerous group of consumers on information put on labels of food products was evaluated as good. Age and the level of education influence the level of knowledge, while the gender Has no effect on it.